El silencio administrativo positivo temporal en materia ambiental a la luz del Decreto-Ley 019 de 2012 - Gómez Rey, Andrés (2023)
The current paper seeks to establish and determine whether article 35 of Executive Order 019 of 2012 has included in environmental law a temporary positive administrative silence indirectly. The essay also purports to determine whether this legal figure can be used when obtaining environmental permits, authorizations, concessions, or licenses. Therefore, the authors seek to analyze new trends in environmental law by focusing on current developments in its recipient, administrative law.